Security, Civilisation and Modernisation: Continuity and Change in the Russian Foreign Policy Discourse. Issue 7 (9th August 2021) - Frear, Matthew; Mazepus, Honorata
Abstract: This study analyses official Russian foreign policy discourses to contribute to our understanding of how Russia portrays its role in world politics and vis-à-vis neighbouring states. Building on previous studies, we offer a new, comprehensive analysis of Foreign Policy Concepts and the annual Presidential Address to the Federal Assembly during President Vladimir Putin's third term (2012–2018). By systematically coding these documents, counting references to particular discourses and undertaking a careful interpretation of the texts, we provide insights about three broader discourses related to foreign policy: the world order and sovereignty; civilisation, identity and values; and economics and modernisation.